Mechanistic insights into the kidney injury in chickens induced by hypervirulent fowl adenovirus serotype 4 - Zhu, Chunhua; Zhou, Jiayu; Chen, Zhen; Chen, Cuiteng; Wang, Ziyue; Yang, Pei; Fu, Guanghua; Liu, Xiaodong; Huang, Yu; Wan, Chunhe (Microbiology spectrum, 2025)
Hypervirulent fowl adenovirus serotype 4 (FAdV-4) has become globally prevalent since 2015 as a predominant pathogen on poultry farms, leading to substantial economic losses for the poultry industry. However, the molecular mechanisms underlying kidney injury induced by FAdV-4 infection remain unclear. In this study, we primarily elucidated the mechanisms of kidney injury induced by FAdV-4 infection in chickens, utilizing both in vitro and in vivo models. Our results demonstrate that FAdV-4 infection in chickens causes degeneration and necrosis of kidney epithelial cells, glomerular injury, and expansion of the endoplasmic reticulum, while also triggering a robust inflammatory response in kidney cells. Notably, we observed the cell-to-cell transmission of virus particles delivered by autophagosome-like vesicles, and the viral infection-induced cellular autophagy facilitated viral replication in the kidney cells. These findings offer a novel perspective to understand the molecular mechanisms of FAdV-4-induced kidney injury and establish a basis for further investigation into the molecular pathogenesis of hypervirulent FAdV-4.